Control of cerium oxidation state through metal complex secondary structures. Issue 12 (7th September 2015) - Levin, Jessica R.; Dorfner, Walter L.; Carroll, Patrick J.; Schelter, Eric J.
Abstract : A series of alkali metal cerium diphenylhydrazido complexes, M x (py) y [Ce(PhNNPh)4 ], M = Li, Na, and K, x = 4 (Li and Na) or 5 (K), and y = 4 (Li), 8 (Na), or 7 (K), were synthesized to probe how a secondary coordination sphere would modulate electronic structures at a cerium cation. Abstract : A series of alkali metal cerium diphenylhydrazido complexes, M x (py) y [Ce(PhNNPh)4 ], M = Li, Na, and K, x = 4 (Li and Na) or 5 (K), and y = 4 (Li), 8 (Na), or 7 (K), were synthesized to probe how a secondary coordination sphere would modulate electronic structures at a cerium cation. The resulting electronic structures of the heterobimetallic cerium diphenylhydrazido complexes were found to be strongly dependent on the identity of the alkali metal cations. When M = Li + or Na +, the cerium(iii ) starting material was oxidized with concomitant reduction of 1, 2-diphenylhydrazine to aniline. Reduction of 1, 2-diphenylhydrazine was not observed when M = K +, and the complex remained in the cerium(iii ) oxidation state. Oxidation of the cerium(iii ) diphenylhydrazido complex to the Ce(iv ) diphenylhydrazido one was achieved through a simple cation exchange reaction of the alkali metals. UV-Vis spectroscopy, FTIR spectroscopy, electrochemistry, magnetic susceptibility, and DFT studies were used to probe the oxidation state and the electronic changes that occurred at the metal centre.